1980
DOI: 10.1177/000348948008900523
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Otitis Media following Middle Ear Inoculation of NonviableStreptococcus Pneumoniae

Abstract: The pathogenesis of otitis media is poorly understood, and the events leading to bacterial invasion of the middle ear cleft and resulting inflammation are a matter of conjecture. While Streptococcus pneumoniae is the most frequent microbe cultured from acute, purulent middle ear effusions, it is infrequently cultured from nonsuppurative serous and mucoid effusion. To explore the possibility that nonviable pneumococci persisting in the middle ear cleft might produce mucosal inflammation, a solution of heat-kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…Further work with the same animal model showed that lipoperoxidation was increased in middle ears injected with heat‐killed pneumococcus 34 . Other authors have demonstrated that inflammatory changes occur in the middle ear after injection with heat‐killed bacteria 35,36 ; this is apparently caused by the products of bacterial cell death. Because lipid peroxidation is known to occur under these conditions, oxygen radicals are further implicated as a contributor to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Further work with the same animal model showed that lipoperoxidation was increased in middle ears injected with heat‐killed pneumococcus 34 . Other authors have demonstrated that inflammatory changes occur in the middle ear after injection with heat‐killed bacteria 35,36 ; this is apparently caused by the products of bacterial cell death. Because lipid peroxidation is known to occur under these conditions, oxygen radicals are further implicated as a contributor to inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza virus inoculated into the nose causes an increase in the frequency of goblet cells in the nasopharyngeal portion of the eustachian tube (185). Increased frequency of goblet cells was also induced by pneumococcal antigens in the bulla of guinea pigs (186). It has also been observed that the ratio of albumin to immunoglobulin can shed light on the stage of infection and further deduce the pathomechanics of infection (187).…”
Section: Inflammation and Ommentioning
confidence: 99%
“…Einige Studien konnten ein modifiziertes Proliferations-, Differenzierungs-und Migrationsverhalten der Keratinozyten der Cholesteatommatrix belegen [3-5, 27, 28]. Das "aggressive" Verhalten der Cholesteatommatrix scheint durch die Freisetzung von Zytokinen und Wachstumsfaktoren aus Zellen des entzündlichen Infiltrats beeinflußt zu werden [1,10,15,18,22,34]. …”
unclassified